The Relationship Between Exposure to Negative Content and the Moral Decline of Gen-Z Among Civics Students at Mataram University - Inni Khaerunnisa’; Bayu Segara Agung; Khaerul Habi; Iqlima Septia Irdani; Hesty Nila Kusnita; Nurmaulida Fajrina (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
In the era of globalization with increasingly rapid technological developments. Along with the presence of Gen-Z, this has led to the development of social media which often presents content from users and not all of it leads to positive things. Some of the content presented often leads to negative things that have a moral impact. In this article, research was conducted to find out whether there was a relationship between exposure to negative content and the moral decline of Gen-Z among Civic Education students at Mataram University. The research method used to collect field data is a quantitative type of correlation which will reveal whether the research objectives were achieved in accordance with the reality that occurred in the field. The results of the Spearman correlation analysis research show a coefficient of 0.0115 with a p-value of 0.9089. Because the p-value is greater than 0.05, the research results show that there is no significant relationship between the frequency of exposure to negative content and the moral impact on PPKn students at Mataram University. Therefore, the null hypothesis (H0), which states that there is no significant relationship between exposure to negative content and moral decline.